Pathogenicity And Molecular Characteristics Of Infectious Bursal Disease Virus Isolates Of Nepal - Sharma, Karuna (2004)

(untitled)
Infectious bursal disease (IBD) outbreak in chickens was first reported in Nepal in 1991. The objective of this study was to identify, characterise and determine the pathogenicity of IBD virus (IBDV) isolates of Nepal. The IBDV isolates, NP2K and NP1SSH were obtained from severe IBD outbreaks in Nepal in 2002. The IBDV isolates were inoculated in specific pathogen free (SPF) chickens and embryonated chicken eggs and identified as IBDV based on conventional methods. The hypervariable region of VP2 gene of NP2K and NP1SSH was amplified by revere transcriptase polymerase chain reaction (RT-PCR). The sequences were aligned, analysed to determine the molecular characteristic of the virus. A phylogenetic tree was constructed and the nucleotide sequences of the isolates were subjected to restriction fragment length polymorphism (RFLP) using computer-generated programme. The NP2K isolate was inoculated into 28-day-old SPF chickens to determine the pathogenicity and response of the bursa of Fabricius, caecal tonsil, thymus and kidney to the IBDV. The NP2K and NP1SSH isolates induced 100% mortality in SPF eggs in passage 1, 2, 3 and 4 post inoculation (pi). In 28-day-old SPF chickens, NP2K isolate produced lesions similar to those of field IBD outbreaks which were more pronounced at day 3 to 5 pi with 55% mortality. A significant decreased (p<0.05) in body weight of IBD group was recorded at day 3 pi. The bursa to body weight ratio was significantly different (p<0.05) at day 10 pi, between the control and IBD groups. The gross and histological lesions in the bursa of Fabricius were more pronounced than those of the thymus, caecal tonsil and kidney. In the bursa of Fabricius severe lesions (score of 5) were recorded at day 2, 3, 4 and 10 pi. The lesions in the thymus and caecal tonsil were moderate to severe (score of 3 to 5) at day 2, 3 and 4 pi, but remained normal or mild at the rest of observation days. In the kidney, only mild lesions were observed at day 3 and 4 pi. The viral antigen was detected only in the bursa of Fabricius and caecal tonsil at day 2, 3 and 4 pi, and was absent in the thymus and kidney using immunoperoxidase technique. The 1326 bp nucleotide and 446 amino acid sequences of NP2K and NP1SSH isolates were compared with other very virulent IBDV (vvIBDV), variant, vaccine, and classical strains of IBDV. The deduced amino acid sequences of NP2K and NP1SSH isolates were very similar to the vvIBDV of Japan (OKYM), Europe (UK661), China (HK61), Israel (IBDVKS), Malaysia (UPM97/61) and Belgium (849VB). Amino acid substitution at four positions were 300 (E to A), 308 (I to F), 334 (A to P) and 438 (I to S) for NP2K and at positions thirteen for NP1SSH at 27 (S to T), 28 (I to T), 31 (D to A), 36 (H to Y), 135 (E to G), 223 (G to S) 225 (V to I), 300 (E to A), 308 (I to F), 334 (A to P), 351 (L to I), 352 (V to E) and 339 (K to N) compare to published vvIBDV strains. Based on RFLP analysis with SspI, StyI, TaqI, StuI, AccI BmstI, MboI and Sac1 and the sequence analysis of NP2K and NP1SSH isolates showed similar characteristics to vvIBDV isolated from Japan, China, Europe and South East Asia. Absence of SspI site was likely due to the change in nucleotide at position 765 from T to C. The NP2K and NP1SSH isolates have BspMI, TaqI, MolI and Stu1 sites in the nucleotide sequence considered as a marker of vvIBDV. The amino acid substitution in different position indicates that a new strain of IBDV is still evolving. The NP2K and NP1SSH isolates were successfully isolated, identified and characterised using both conventional and molecular techniques as vvIBDV strain of serotype 1. The NP2K isolate produced severe lesions in the bursa of Fabricius and followed by caecal tonsil, thymus and kidney. The origin of the virus could be from China, Europe, Japan, or South East Asia. The accession numbers of the NP2K and NP1SSH isolates are AY 367560 and AY 605264 as provided from the gene bank, respectively.